Diversity and Ecology of Zooplankton in Mumbri creek of South Konkan, Maharashtra, India - Dekate HM; Baviskar RN (International Journal of Life Sciences, 2016)
The present investigation was carried out in Mumbri Creek of Sindhudurg district (Lat. 16º 21’ N. Long. 73º 25’ E). The main aim of this work is to find out the productivity of the said creek. The zooplankton plays a very important role in food chain and food web. Most of these are small, microscopic organisms which feed on phytoplankton and ultimately become fish food. The Copepods, Mysids and Chaetognaths are predominantly present throughout the year. Zooplankton provides food for the masses; they get proteins, minerals, vitamins, etc. to the in developing countries. During the non-availability of fish or otherwise the locals depend on zooplankton for food. The work was investigated in Jan. 2015-Jan. 2016.